Digital Religious Public Sphere and Qur’an-Hadith Literacy: A Study of Muslim Students - Fikri Hamdani; Muhammad Nawir (ZAD Al-Mufassirin, 2026)
This study examines the transformation of Qur’an-Hadith literacy among Muslim students in the digital religious public sphere. Employing an explanatory sequential mixed-methods design, the study involved 120 students at Universitas Islam Negeri Datokarama Palu as questionnaire respondents and 12 purposively selected informants drawn from the Faculty of Ushuluddin, Adab, and Dakwah, Faculty of Tarbiyah and Teacher Training, Faculty of Sharia, Faculty of Islamic Economics and Business, and Ma’had al-Jami’ah/campus-based religious study communities. Quantitative data were analyzed using descriptive statistics through percentage tabulation, while qualitative data were examined through manual thematic analysis. The findings indicated that 73.3% of students engage with Qur’an-Hadith content via digital media at least three times a week. YouTube emerged as the predominant platform (35.0%), followed by TikTok (25.8%), Instagram (17.5%), and digital Qur’an/tafsir/hadith applications (15.0%). Audiovisual platforms were used by 78.3% of respondents, indicating that students prefer visual, concise, and algorithmically recommended religious content. Nevertheless, 74.2% of respondents regarded conventional learning as the most authoritative source for deeper Qur’an-Hadith understanding. The study concluded that students’ Qur’an-Hadith literacy reflects a hybrid pattern: in which digital media function as an initial point of access, while conventional academic and kitab-based learning remains central to verification, interpretive depth, and epistemological legitimacy.